Nationwide cross-sectional study on brucellosis sero-prevalence in buffaloes using competitive ELISA - SHOME, RAJESWARI; PATIL, SHARANGOUDA; SHAMSHAD, SAMER; SKARIAH, SOMY; SAHIB, MUNEERA MOHAMED; SHANMUGAM, G; BARMAN, NAGENDRA NATH; BORA, DURLAV PRASAD; SHOME, ARIJIT (The Indian Journal of Animal Sciences, 2024)
Brucellosis is a bacterial disease caused by various Brucella species, which mainly infect bovines (cattle, buffalo), small ruminants (sheep, goat), swine, and dogs and humans. Earlier studies have reported brucellosis sero-prevalence only in cattle or both in cattle and buffaloes (bovine brucellosis) and actual disease burden in buffaloes was not available. The current study aimed to record countrywide brucellosis sero-prevalence in Indian buffaloes using competitive ELISA (cELISA). For the study, 1086 female buffalo (Bubalus bubalis) serum samples were collected from the top 10 states of India having the highest buffalo population. Overall, samples were drawn from 62 districts, 104 blocks and 242 epiunits from five regions of the country ({Punjab-100, Haryana-109, Uttar Pradesh-101, Rajasthan-100, Gujarat-156, Andhra Pradesh-100, Madhya Pradesh-110, Maharashtra-108, Karnataka-102, Andhra Pradesh-100 and Tamil Nadu-100)}. Samples were tested for anti-brucella antibodies using in-house developed monoclonal-based competitive ELISA (cELISA). Overall, apparent prevalence (AP) of 15.38% (CI-95%;13.35-17.64) and true prevalence (TP) of 15.85% (CI-95%; 13.77-18.19) were recorded. Sero-prevalence was highest in Punjab state (AP:57%; 47.22-66.27) in the Northern region and lowest in Madhya Pradesh (AP:0.90; 0.16-4.97) state of Central region with some of the districts displaying up to 90% and 70%, seropositivity in the Punjab state. Low brucellosis prevalence was noted in young (2.1 to 5 years) and older age groups of animals (11.1 to 13 years) and significantly high in the age group between 8 to 11 years (32.23%). The highest brucellosis seropositivity was observed in buffalo breeds such as Nagpuri and Murrah (28.79% and 20.67%), respectively and significant association was noted among four breeds. In conclusion, India has the highest buffalo population with very high-yielding buffalo breeds (109.85 million). Periodical surveillance is essential to detect and control brucellosis in buffaloes.-the pride species of the country.